Implementasi Pembelajaran Kreatif Di Man 1 Kota Bitung - Abas, Ramlah (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2021)
The purpose of this research to know the results of the creative learning at MAN 1 Bitung City. The research methodology is a qualitative approach using principals of Madrasah informants, teacher of religious education, and teacher of general subject. The research procedure is collecting data, and drawing conclutions. After the data is collected then test the validity of the data. The results are: 1) the creative learning process at MAN 1 Bitung is the teacher designs learning materials so the students are motivated to do creative activities. The learning method is talking stick, using the guessing method, and learning media such as cellpones, LCDs, 2) Habituation activities at MAN 1 Bitung City are: a)After the morning parade (Monday and Thursday) praying dhuha together; b) pray before starting the lesson: c) Tadarrus Alqur’an 10 minutes before starting the lesson; d) Dhuhur prayer together; e) Giving Zakat or alms during the holy month of Ramadhan; f) Breaking the fast together during the holy month of Ramadhan; g) implementation of slaughter of qurban animal (Idul Adha) for students and all staff of MAN 1 City of Bitung. In conclution: creative learning in MAN 1 Bitung City is by learning in the classroom and habituation activities for both teacher and student in MAN 1 Bitung City.